Detection of Staphylococcus aureus Biofilm from Subclinical Mastitis Milk - Lesmana, Muhamad Arfan; Qosimah, Dahliatul; Murwani, Sri (Veterinary Biomedical and Clinical Journal, 2019)
One of S.aureus's virulence factors is biofilm formation. When biofilms are formed, the bacteria will undergo phenotypic changes that require higher concentrations of antibiotics to inhibit proliferation. Phenotypic changes will lead to increase the production of extracellular matrix and multilayered colonies as well as decrease of metabolic rates, multiplication and polymicrobial colonization resulting in recurrent infection in the host and difficulty being treated with antibiotics due to resistance. The aim of this research was to know the formation of bacterial biofim by slime and quantitative by microplate titer method. The research method was qualitative descriptive using 27 samples of Staphylococcus aureus  with characterized from mastitis infected milk. The bacteria were grown on CRA (Congo Red Agar) media to observe the slime biofilm through bacteria black colony followed by MicrotiterPlate  method  with 570nm wave lenght. The results showed that 27 samples of Staphylococcus aureus which positive to form slime biofilm were 10 samples and continued to microtiter plate showed 3 positive samples of biofilm. The conclusions of this study, Staphylococcus aureus in subclinical mastitis milk samples were positive to form biofilms.